Practical training for language and literature teachers: Towards adidactic and collaborative model for teaching literacy - Castro-Cifuntes, Mauricio (2025)
The study examines the initial training of 32 future Language and Literature teachers of a university in Chile, from an intermediate stay in educational centers under a methodology in pairs (n=16). Its objective is to analyze the conceptions of collaborative work of teachers in training, considering previous trajectories, models and effective strategies. The research follows a qualitative design and employs the technique of thematic analysis. The results reveal that the experiences lived during schooling mark models of understanding to install collaborative learning strategies. Likewise, a difference is observed between the activities implemented by the collaborating teachers and the trainee teachers. On the other hand, with respect to teaching, it is concluded that co-teaching is a methodology present in 73% of the practice classrooms, however, with variations in the levels of significance. Finally, the research proposes a formative model of collaborative practice.